A Troubling Diagnosis of Verrucous Squamous Cell Carcinoma ("the Bad Kind" of Keratosis) and the Need of Clinical and Pathological Correlations: A Review of the Literature with a Case Report. (12th October 2010) - Santoro, A.; Pannone, G.; Contaldo, M.; Sanguedolce, F.; Esposito, V.; Serpico, R.; Lo Muzio, L.; Papagerakis, S.; Bufo, P.
Abstract : Verrucous carcinoma (also known as Ackerman tumor) is an uncommon exophytic low-grade well-differentiated variant of squamous cell carcinoma. This neoplasm typically involves the oral cavity, larynx, genitalia, skin, and esophagus. It is well known for its locally aggressiveness and for its clinically slow-growing behaviour with minimal metastatic potential. Verrucous carcinoma of oral cavity is so closely aligned with the use of snuff and chewing tobacco that it has been called the "snuff dipper's cancer". Recent studies have proved the role of HPV. The typical clinical presentation of oral verrucous carcinoma has long been known, as its remarkably innocuous appearance and biological behaviour. In this work, we report a review of the scientific literature and describe a troublesome case of oral verrucous cancer.